Pengaruh Digitalisasi terhadap Aktifitas Pembelajaran Pendidikan Jasmani Olahraga dan Kesehatan pada Lingkungan Pendidikan SMP Negeri 1 Sedayu - Ginanjar Nugraheningsih; Adriyansyah Bimantara (EduInovasi: Journal of Basic Educational Studies, 2024)
This research aims to determine the impact of digitalization on the learning process through several aspects: (1) knowledge, (2) application, and (3) utilization in PJOK (Physical Education, Sports, and Health) learning. This is a descriptive quantitative study using the survey method. The population consists of 221 students from grades VIII A-G at SMP Negeri 1 Sedayu. The sample includes 120 students selected through incidental sampling. Data collection techniques involve the use of a Likert scale with ratings of SS (5), S (4), KS (3), TS (2), and STS (1). The research instrument is a questionnaire tested for validity and reliability. Data analysis is conducted using percentages (%). The results show that the impact of digitalization on the PJOK learning process at SMP Negeri 1 Sedayu is categorized as high in terms of (1) knowledge aspect at 71.35%, (2) application aspect at 69.44%, and (3) utilization aspect at 67.19%. Based on these findings, it can be concluded that the influence of digitalization on the PJOK learning process in the educational environment of SMP Negeri 1 Sedayu is categorized as high in the aspects of (1) knowledge, (2) application, and (3) utilization. Therefore, this research aims to assist PJOK subject teachers in considering the use of digitalization in the learning process from various aspects.